Non-competitive NMDA antagonist MK-801 prevents memory reconsolidation impairment caused by protein synthesis inhibitors in young chicks - Tiunova, A. A.; Bezriadnov, D. V.; Anokhin, K. V. (Frontiers in Pharmacology, 2024)
In our study, we examined the molecular mechanism of memory reconsolidation in one-day-old chicks using the tools of neurpharmacolology. It is known that memory reactivation makes it labile, which is usually followed by its reconsolidation. Interference with the molecular mechanisms of consolidation, such as protein synthesis, has been shown to impair this process.Our study using a one-trial passive avoidance learning model in newborn domestic chicks showed that systemic administration of the noncompetitive NMDA receptor antagonist MK-801 before reminder treatment successfully rescued memory reconsolidation impaired by protein synthesis inhibitors. These results allow us to hypothesize a dual role of NMDA receptors in memory reconsolidation in young chicks: their involvement in both protein synthesis-independent memory destabilization during retrieval and protein synthesis-dependent stabilization after its updating.